THE INFLUENCE OF BUSINESS ACTIVITIES ON THE APPLICATION OF SUSTAINABLE ACCOUNTING IN COMPANIES IN DENPASAR CITY - Ni Luh Putu Mita Miati; I Nyoman Sutapa; I Gde Agung Wira Pertama (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
In sustainability accounting, environmental issues are always raised by many events that have a serious impact on the environment that harm the health and economic interests of the community. Some previous researchers have conducted research on sustainability accounting so researchers will provide additional studies in MSME objects where this object is still little researched. The theory used in this study is the Triple Bottom Line theory. This research will conduct testing in accordance with the formulation of the problem that has been formulated using a quantitative paradigm using multiple linear regression test tools to test the hypotheses that have been proposed. The population in this study is MSMEs in the Denpasar district as many as 29,549 with samples taken from as many as 100 MSMEs. The research variables in this study are Supply Chain Characteristics, Business Characteristics, the application of the company's accounting system, and the application of sustainable accounting. The method to analyze the data in this study used Partial Least Square (PLS). Based on the results of the study, it can be concluded that supply chain characteristics have a positive effect on the application of sustainable accounting, while the business characteristics and the application of the company's accounting information system respectively do not have a significant effect on the application of sustainable accounting. Suggestions for future researchers to be able to redevelop the results of this study that do not have a significant effect